A multiscale microstructure model of cement paste sulfate attack by crystallization pressure. (13th July 2017) - Feng, Pan; Bullard, Jeffrey W; Garboczi, Edward J; Miao, Changwen
Abstract: A recent microstructural model of near-surface external sulfate attack on cement paste is modified to incorporate diffusive ionic transport between the surface and interior of a macroscopic specimen that has been hydrated for 100 d prior to exposure to sulfates. The model estimates the driving force for local expansive growth of the Al 2 O 3 − Fe 2 O 3 -tri (AFt) phase in terms of crystallization pressure, and the strain and stress fields are tracked within the microstructure with micrometer-scale resolution using a linear elastic finite element model. Damage induced by expansion modifies both the local effective transport properties and linear elastic properties of the local microstructure at different depths, and thereby potentially alters the rates of sulfate ingress and expansion. Therefore, the progress of phase transformations and expansion from the surface to the interior of the porous material is dictated by the rate of ingress of concentration fronts of both sulfate ions and pH, which do not necessarily coincide. The model is used to relate microscopic changes in the structure of cement paste, induced by ingress of sodium sulfate solutions of different concentrations, to the macroscopic expansion, and the results are compared with previous models and published experimental data. The model demonstrates what has previously been assumed in sulfate-attack models, namely that volumetric expansion of macroscopic paste samples in the early stages of sulfate attack is a linear function of the mass of AFt phase precipitated. In addition, the model captures the main features of the evolution of local elastic and transport properties within a macroscopic paste sample, showing an apparently parabolic dependence on depth of the local Young's modulus and local formation factor.